Seropositivity of Hepatitis B Surface Antigen among Jaundice Children - Ijaz Ahmed, Musa Hassan, Kaynat Khalid, Mohammad Mohsin Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of Hepatitis B Virus antigen among jaundiced children admitted in pediatric unit. Materials and Methods: A total of 180 children, aged 1-15 years admitted with jaundice in the hospital were included from Jan-2022 to May-2022. While children pre-vaccinated against Hepatitis B as these children are pre-diagnosed for negative HVB antigens or children suffering from any kind of malignancy e.g. hepatocellular carcinoma or gastro-intestinal carcinoma were excluded. Blood samples were taken from every children by a phlebotomist and were sent to the central laboratory of the hospital for HBV detection. Enzyme-linked Immunosorbent Assay (ELISA) test was used to confirm diagnosis of seropositivity of HBV. Results: The mean age study was 8.89+4.13 years. There were more males as compared to females in this study. There were 115 (63.9%) males and 65 (36.1%) females. The mean duration of jaundice in this study was 13.6+10.25 days. Hepatitis B virus infection was diagnosed in 33 (18.3%) patients. HBV antigen was detected in 26 (22.6%) males and only 7 (10.8%) girls (p-value 0.04). Conclusion: Children with jaundice have a greater risk of hepatitis B virus seropositivity (18.3%). Male children are more likely than females to get infected with HBV.